3 - Negotiating the search for diagnosis and healing tuberculosis in Namibia. A case study of a Ju/’hoansi speaking man. - Diana Gibson (African Sociological Review, 2010)
This case study of tuberculosis among Ju/’hoansi speakers in a small village in Otjodzondjupa district, namibia, shows how different notions concerning tuberculosis and TB-like complaints become a area of uncertainty and even contention in a situation where tuberculosis education is good but diagnostics, and by extension treatment, are not always easily accessible. The paper argues that culturalism in the health services turns attention away from the socio-economic and political aspects of tuberculosis. it furthermore shows that Ju/’hoansi speakers have to turn to plant medicines to deal with their ill health when the interface with the health care ser- vices become problematic. Plants are understood as standing in a particular relationship with humans andwith nature as well. Yet the use of plant medicines is also a terrain of medicinal knowledge andpractice contested by the health care services as potentially unsafe and counter- productive to TB treatment.